Amplificação da polarização de Macrófagos M1 e inibição do desenvolvimento tumoral pelo tratamento com Aminoguanidina - NASCIMENTO, Johnny Ramos do (2018)
Nitric oxide (NO), produced by M1 macrophages, has a dichotomous role in the control of malignant cells, stimulating or inhibiting their development according to their concentration and/or origin. The aim of this work was to evaluate the effect of inhibition of NO production on macrophage polarization and on tumor development. Initially, the cytotoxicity of aminoguanidine hemisulfate (AG) in Raw 264.7 cells was evaluated. Next, the effective concentration for NO inhibition by M1 macrophages was evaluated. After these assays, the concentration of 1mM AG was chosen. Following, it was investigated whether AG interferes in the M1 and M2 macrophages polarization, based on the NO and cytokines production and the CD80, CD86 and iNOS expression. Subsequently, treatment with AG at a dose of 100 mg/kg, v.o. in 3 different treatment times, initial (AGI), final (AGF) and continuous (AGC), of Swiss mice bearing the ascitic (n = 30) and solid (n = 54) forms of the Ehrlich tumor. The Clean and Control groups received no treatment and the CICLO group was treated with cyclophosphamide monohydrate (Genuxal - Baxter Oncology) at a dose of 25mg/kg, i.p. Survival was evaluated in animals with ascites tumor. In the animals with solid tumor, the tumor growth area was monitored and after the euthanasia the serum collection was done for the biochemical analyzes; removal of paw and ear with tumor for histopathological analysis and removal of lymphoid organs and peritoneal lavage to verify cellularity and culture. AG was not able by itself to polarize Raw264.7 macrophages, without altering the production of cytokines, nor the CD80, CD86 and iNOS expression. However, iNOS inhibition in macrophages polarized into the M1 profile enhanced the CD80, CD86 and iNOS expression. The production of inflammatory cytokines, IL-6, MCP-1 and IL-12p70, and the regulator, IL-10, was also increased. M1 macrophages did not produce NO in the presence of the inhibitor in 24 and 48h, however after the withdrawal of the inhibitor, they began to produce NO, being higher in 48 hours in relation to the non-inhibited M1 group. In the animals bearing the ascites tumor, the iNOS inhibitor was not able to increase survival or life expectancy. On the other hand, in the animals bearing the solid tumor, a delay in tumor growth was observed in the AGI and AGC groups. In the histopathological analysis, the presence of blood vessels was lower in the AGI, AGF and AGC groups. In all groups there was a predominance of polymorphonuclear cell infiltration, necrosis and edema. There was no alteration in the cellularity of the lymphoid organs, except for the cellularity of the draining lymph node, which was lower in the AGI and AGC groups. Therefore, blocking NO production by iNOS in vitro enhances the polarization of M1 macrophages and the inhibition of this enzyme in the early stages of Ehrlich solid tumor implantation impedes the angiogenesis process, delaying tumor progression.